Hold still : a memoir with photographs - Mann, Sally, 1951- (2015)
A memoir and family history from acclaimed photographer Sally Mann. Her luminous photographs have become icons of modern art, but Mann also possesses a fearlessness and clarity of vision in her writing as well. As she sets out to understand her parents, Mann unravels threads that lead to discoveries about generations past, the marks they made on the world, and how these reverberate in her life and work today.
Prologue: The Meuse -- Family ties: the importance of place. The sight of my eye ; All the pretty horses ; The bending arc ; The family of Mann ; The remove ; Our farm, and the photographs I took there ; Hold still ; Ubi amor, ibi oculus est -- My mother: memory of a memory past. A sentimental welshman ; Uncle Skip and the little dears ; The southern landscape -- Gee-Gee: the matter of race. The many questions ; Hamoo ; Smothers ; The kid on the road ; Who wants to talk about slavery? -- My father: against the current of desire. The munger system ; Leaving Dallas ; Mr. death and his blue-eyed boy ; World traveler, interesting gent ; The cradle and the grave ; Bearing witness ; The sublime end ; The x above my head -- Postscript: Exhibit A, Exhibit B.
Includes bibliographical references (page 478)
Keywords: Mann, Sally, -- 1951-; Mann, Sally, -- 1951- -- Family; Women photographers -- United States -- Biography; Photographers -- United States -- Biography; Photography, Artistic; Portrait photography; Autobiographies; Biography